Factors influencing pupils’ retention in public primary schools: a case of Trans Mara East Sub-County– Narok County, Kenya - Kipkemboi, John (Strathmore University, 2021)
Education plays a vital part in the growth and progression of any country’s economy. Kenya has implemented free primary education on three separate occasions. The policy aimed to upsurge the enrolment rate in public primary schools in the nation and enhance their retention rate in these institutions. However, the policy has faced several challenges, which have resulted in a decrease in the retention rates of pupils in these schools. The study aimed to analyze the factors influencing the retention of pupils in public primary schools in Trans Mara East Sub-county of Narok County. The study's specific objectives were: to assess the influence of economic factors, geographical factors, and socio-cultural factors on the retention of pupils in public primary schools in Trans Mara East Sub-county. The researcher utilized a descriptive research design to determine the association existing amid dependent and independent variables. The target populace for the study comprised of school heads, parents, pupils, board and committee members and sub-county directors in Trans Mara Sub-county. The total target population was 2029. The investigator utilized a multistage sampling method where stratified and convenience sampling methods were utilized to select different sizes of samples for the investigation. Questionnaires were employed in collecting primary data from the sub-county. Inferential and descriptive statistics were used to present the results. The study’s outcomes are expected to benefit the ministry of education, school administrators, County government of Narok and future researchers. The findings revealed that separately, economic, social, cultural, and geographical proximity positively and significantly influence learner retention. However, when all the variables are combined, only social-cultural factors had a significant predictive ability to influence learner retention. Overall, the study concluded that economic factors, social-cultural factors and geographical proximity have a positive and significant relationship influence on learner retention. Based on the findings, the study recommended that the national government in collaboration with the Narok County government, should make policies aimed at enhancing the economic actitivies of the people living in this region, should also advocate for family planning to ensure that parents give birth to children that they can provide quality basic life, should eliminate female genital mutilation, early marriages, and support both girl and boy education. They should build more schools, improve the infrastructure of existing schools, and ensure the availability of quality school facilities such as toilets.
A Dissertation submitted in partial fulfilment of the requirements for the Degree of Masters in Public Policy and Management in Strathmore Business School
Keywords: Public primary schools; Pupils; Trans Mara East Sub-County– Narok County, Kenya